NMR-spectral and structural characteristics of new pyridoxine derivatives - A.S. Tarasov; I.Z. Rakhmatullin; Yu.G. Shtyrlin; V.V. Klochkov (Учёные записки Казанского университета: Серия Естественные науки)
The relevance of the study is determined by the fact that in the last decade pyridoxine derivatives have been widely used for the synthesis of molecules with important biological and physical properties. However, synthesis of the compounds with desirable biochemical or physical properties often requires information about their spatial structure and conformational mobility. NMR spectroscopy is a powerful tool for conformational analysis of biologically important samples, such as pyridoxine derivatives, in solution. Two new pyridoxine derivatives were studied using high-resolution nuclear magnetic resonance (NMR) spectroscopy: one-dimensional 1H NMR spectroscopy, two-dimensional 1H-1H COSY NMR techniques, dynamic 1H NMR. The lineshape analysis of obtained spectra was carried out and the values of rate constants of the exchange of assumed conformational processes were calculated in the WinDNMR computer program. The thermodynamic parameters characterizing the transitions between the observed conformers and the types of conformational processes are determined. Based on the results of the study, the following conclusions were made. The studied compounds are involved into two types of conformational exchange processes: restricted rotations of the dinitrophenyl fragment around the C12–O bond and twist-twist interconversions of the seven-membered ring (for compound 1). Comparison of the obtained results shows that the dynamics of neighboring conformational processes have a significant effect on each other. It was established that the influence of the “twist” process in compound 1 leads to a decrease in the rotation barrier by 10 kJ/mol. This observation can be explained by the increased steric hindrance of the substituents raising the energy of the ground state, and thus lowering the activation energy barrier.